Distribution of carbon and nitrogen in forest floor components in Pinus radiata plantations of different ages in South Australia. Issue 2 (3rd April 2017) - Jeong, J.; Bolan, N. S.; Harper, R. J.; Kim, C.
ABSTRACT: This study was conducted to evaluate the effects of plantation age on the distribution of carbon (C) and nitrogen (N) in forest floor components in radiata pine ( Pinus radiata D. Don) plantations. Forest floor samples from plantations of three age classes (13-year-old; 27-year-old; 41-year-old) with various site qualities (II–VII) were collected from the Kuitpo radiata pine plantations in the Mount Lofty forest region of South Australia. The C concentrations of the forest floor components were significantly higher in the 41-year-old plantation than in the 13-year-old plantation, whereas the N concentrations were significantly lower in the 41-year-old plantation than in the 13-year-old plantation, except for the needle component. The C and N content of needles was significantly larger in the 13-year-old plantation than in the 41-year-old plantation, whereas fine woody materials, such as branches and bark, contributed less to the total C and N contents in the 13-year-old plantation. The total C content of the forest floor did not significantly differ with age, whereas the N content was significantly affected by age in the radiata plantations. The results reflect the existence of considerable variation in the quality and quantity of the C and N in forest floor components associated with different ages of radiata pine growing in sites of various qualities.